Correlation between APRI, FIB-4 and GPR Indices to Fibroscan and HBeAg Status in Patients with Chronic Hepatitis B - Erlina, Rina; Wardhani, Puspa; Puspitasari, Yessy; Kholili, Ulfa (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Liver fibrosis is a complication of chronic hepatitis B. Early detection of liver fibrosis is important for therapy. The aspartate aminotransferase index (AST)-to-platelet ratio index (APRI) and the fibrosis index based on 4 factors (FIB-4) in chronic hepatitis B have been widely studied despite the inconsistent results. Research on other serum markers is extensively carried out, including Gamma-Glutamyl Transpeptidase (GGT)-to-platelet ratio (GPR). Previous studies have shown that the GPR index was more accurate than APRI and FIB-4. HBeAg status is an indication for therapy. There have not been many studies on the correlation of serum markers with HBeAg status. This study aimed to determine the correlation of APRI, FIB-4, and GPR with Fibroscan and HBeAg status in chronic hepatitis B patients. A cross-sectional study was carried out from June to September 2020 and found 50 chronic hepatitis B patients. Platelet count was measured using a Sysmex XN-1000 hematology device; AST, alanine aminotransferase (ALT), and GGT levels were measured using the Dimension RXL clinical chemistry device; and the degree of fibrosis was determined using transient elastography (Fibroscan). Spearman correlation test was used in this study for the correlation analysis. The results showed a significant correlation between APRI, FIB-4 and GPR indices with Fibroscan (r=0.454, p 0.001; r=0.610, p < 0.001; r=0.540, p < 0.001, respectively). A significant correlation was found between APRI, FIB-4 and GPR indices with negative (-) HBeAg (r=0.486, p 0.004; r=0.648, p < 0.001; r=0.595, p < 0.001, respectively). In addition, a significant correlation was found between FIB-4 and positive (+) HBeAg (r=0.499, p 0.049), but no correlation was found between APRI and GPR with positive (+) HBeAg (r=0.295, p 0,267; r=0.386, p 0.140, respectively).